Incidence and risk factors for phaeochromocytoma diagnosis in dogs under primary veterinary care in the UK - Martin Litviakov; Dan G. O’Neill; Dave C. Brodbelt; Sara Galac; Floryne O. Buishand (PLoS ONE, 2025)
Phaeochromocytoma (PCC) is a tumour arising from the adrenal gland in dogs that can be challenging to diagnose. This study aimed to describe the incidence risk, breed predispositions and other demographic risk factors associated with the diagnosis PCC in dogs receiving primary veterinary care in the UK. All anonymised VetCompass Programme electronic health records from dogs receiving primary veterinary care in the UK during 2019 were included. Demographic risk factor analysis used multivariable logistic regression modelling. Out of a study population of 2,250,741 dogs, 92 were confirmed as PCC cases at any time point. The estimated 2019 incidence risk for PCC diagnosis was 1 per 100,000 dogs. The Soft-Coated Wheaten Terrier, German Pointer and Miniature Schnauzer showed significant breed predispositions for the diagnosis of PCC compared with crossbred dogs. Terrier breeds and breeds predisposed to other endocrine tumours were found to have increased odds of being diagnosed with PCC. Furthermore, neutered males and dogs aged between 9 and under 15 years were also associated with increased odds of PCC diagnosis. This study is the first to describe the epidemiology of PCC in dogs receiving primary veterinary care, providing new information concerning demographic risk factors and helping to improve clinical recognition of PCC for veterinary clinicians. Moreover, results from this study facilitate further research in the possible links of canine PCC with other canine endocrine tumours and the existence of concurrent endocrine neoplasia in dogs. Additionally, the results allow researchers to more robustly define useful PCC study populations for future comparative oncology studies.